MENYOAL HUKUMAN MATI DALAM ISLAM (SEBUAH TINJAUAN DARI AYAT DAN HADIS) - Daipon, Dahyul (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2015)
There are a couple of Regulation Legislation concerning the death penalty for a criminal offense in Indonesia. Act like No.7/Drt/1955 on Economic Crime, Law no. 22 of 1997 concerning the Crime Narcotics and Psychotropic Substances, Law no. 31 of 1999 as amended by Law no. 20 of 2001 on the Corruption, Law no. 26 of 2000 concerning the Crime Against Human Rights, Government Regulation Anti-Terrorism Act which was passed into law. There are two camps that emerged in the application of the death penalty; The first is a faction who opposed the application of the death penalty in law in Indonesia, with a variety of reasons that mostly associated with human rights abuses (human rights) the right to life. On the basis of Article 28A of the 1945 Constitution which states